2004
DOI: 10.1021/ja048114o
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Engineering Approach To Forming Cocrystals of Amine Hydrochlorides with Organic Acids. Molecular Complexes of Fluoxetine Hydrochloride with Benzoic, Succinic, and Fumaric Acids

Abstract: A crystal engineering strategy for designing cocrystals of pharmaceuticals is presented. The strategy increases the probability of discovering useful cocrystals and decreases the number of experiments that are needed by selecting API:guest combinations that have the greatest potential of forming energetically and structurally robust interactions. Our approach involves multicomponent cocrystallization of hydrochloride salts, wherein strong hydrogen bond donors are introduced to interact with chloride ions that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
420
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 572 publications
(429 citation statements)
references
References 27 publications
9
420
0
Order By: Relevance
“…Carboxylic acids were selected based on their known ability to form strong hydrogen bonds to chloride ion, 135 and indeed cocrystals were found that contained fluoxetine hydrochloride and the pharmaceutically acceptable benzoic, fumaric, and succinic acids. 124 While the anticipated hydrogen bond between the COOH group of the guest and the chloride ion were present in each of the cocrystal structures, it should be noted that other, unanticipated hydrogen bond motifs are also present and important to the overall stability of the structures (exemplified by the succinic acid cocrystal shown in Figure 12). 124 The point is that, even though the chloride ion was used in this case as the focus of efforts to establish new cocrystal structures, it was still not possible to predict exactly the structures and hydrogen bond motifs that eventually resulted.…”
Section: Examples Of Cocrystals From the Literaturementioning
confidence: 98%
See 2 more Smart Citations
“…Carboxylic acids were selected based on their known ability to form strong hydrogen bonds to chloride ion, 135 and indeed cocrystals were found that contained fluoxetine hydrochloride and the pharmaceutically acceptable benzoic, fumaric, and succinic acids. 124 While the anticipated hydrogen bond between the COOH group of the guest and the chloride ion were present in each of the cocrystal structures, it should be noted that other, unanticipated hydrogen bond motifs are also present and important to the overall stability of the structures (exemplified by the succinic acid cocrystal shown in Figure 12). 124 The point is that, even though the chloride ion was used in this case as the focus of efforts to establish new cocrystal structures, it was still not possible to predict exactly the structures and hydrogen bond motifs that eventually resulted.…”
Section: Examples Of Cocrystals From the Literaturementioning
confidence: 98%
“…124 While the anticipated hydrogen bond between the COOH group of the guest and the chloride ion were present in each of the cocrystal structures, it should be noted that other, unanticipated hydrogen bond motifs are also present and important to the overall stability of the structures (exemplified by the succinic acid cocrystal shown in Figure 12). 124 The point is that, even though the chloride ion was used in this case as the focus of efforts to establish new cocrystal structures, it was still not possible to predict exactly the structures and hydrogen bond motifs that eventually resulted. In fact, not all pharmaceutically acceptable carboxylic acids that were used with fluoxetine hydrochloride in screening experiments provided cocrystals, confirming that hydrogen bonding between the acid group and the chloride ion is not a sufficient condition for cocrystal formation.…”
Section: Examples Of Cocrystals From the Literaturementioning
confidence: 98%
See 1 more Smart Citation
“…A number of cocrystals of APIs with different co-formers formed by different methods have been reported and it was shown that the solid-state interactions between the two compounds are mainly based on hydrogen bonds Childs et al, 2004;Lu and Rohani, 2009;Padrela et al, 2009;Paluch et al, 2011;Trask et al, 2005;Wenger and Bernstein, 2008). We have previously shown that the sulfoxide (S=O) functionality, common in a significant number of APIs, is a potent hydrogen bonding acceptor and forms cocrystals in association with a wide variety of amino (NH) functional groups (Eccles et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Intrinsic dissolution tests have been reported for numerous single component pharmaceutical materials (Avdeef and Tsinman, 2008;Mauger et al, 2003;O'Connor and Corrigan, 2001;Yu et al, 2004) whereas little literature is found for cocrystals (Childs et al, 2004;Jung et al, 2010;Lee et al, 2011;Rahman et al, 2011). The intrinsic dissolution rate is based on measurements of powder compacts of known surface area under conditions of controlled hydrodynamics (Healy et al, 2002) and is described as particle-size independent (Hendriksen and Williams, 1991;Wood et al, 1965).…”
Section: Introductionmentioning
confidence: 99%